Internal compared with external drainage of pancreatic duct during pancreaticoduodenectomy: a retrospective study - Meng, Guangxing; Xing, Qianzhe; Yuan, Qiang; Du, Zhi; Wang, Yijun; Meng, Hua (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Objective: To compare internal with external drainage of the pancreatic duct during pancreaticoduodenectomy with regard to the incidence of postoperative pancreatic fistula (POPF) and other complications. Methods: We retrospectively analyzed 316 patients who underwent pancreaticoduodenectomy with a placed drainage tube (external, n=128; internal, n=188) in the pancreatic duct from 1 January 1999 to 31 December 2011 in Tianjin Third Central Hospital of China. The incidence of POPF and some other complications were compared. Results: There was no difference in the incidence rates of POPF between those given an internal or external drainage tube (P=0.788), but POPF was more severe in the former (P=0.014). Intraperitoneal bleeding rate was also higher in the patients with internal drainage (P=0.040), but operative time and postoperative hospitalization were longer in those with external drainage (P=0.002 and P=0.007, respectively). There was no difference between the groups with regard to the incidence rates of gastrointestinal bleeding, delayed gastric emptying, pulmonary infection, or incision infection and in-hospital mortality. Conclusions: External drainage of the pancreatic duct during pancreaticoduodenectomy can decrease the severity of POPF, but operative time and postoperative hospitalization will be extended.